2021
DOI: 10.1016/j.ajo.2020.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Intraoperative Optical Coherence Tomography of Crystalline Lens Diameter, Thickness, and Volume with Biometry and Age

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 54 publications
0
23
1
Order By: Relevance
“…One may argue that RLE eyes and cataract surgery eyes might not be considered equivalent and may have wide variations in lens thickness (LT), ACD, aqueous depth (AQD) and effective lens position (ELP). However, although recent studies have reported the expected correlation among lens volume (LV) and LT with aging, 30 others observed that neither LT nor lens volume or lens vaulting had a strong correlation with postoperative ACD. 31,32 In fact, we have observed that the greatest predictor for postoperative ELP using sweptsource OCT biometry (IOL Master 700, Carl Zeiss) is actually a metric called lens meridian position (LMPdistance from the corneal epithelium to the intersection of the anterior and posterior lens) measured by intraoperative spectral-domain OCT (Catalys ® Precision System, Johnson & Johnson Vision); in these eyes, ELP displayed no correlation to intraoperative lens volume (Gouvea, et al, unpublished data, 2021).…”
mentioning
confidence: 94%
“…One may argue that RLE eyes and cataract surgery eyes might not be considered equivalent and may have wide variations in lens thickness (LT), ACD, aqueous depth (AQD) and effective lens position (ELP). However, although recent studies have reported the expected correlation among lens volume (LV) and LT with aging, 30 others observed that neither LT nor lens volume or lens vaulting had a strong correlation with postoperative ACD. 31,32 In fact, we have observed that the greatest predictor for postoperative ELP using sweptsource OCT biometry (IOL Master 700, Carl Zeiss) is actually a metric called lens meridian position (LMPdistance from the corneal epithelium to the intersection of the anterior and posterior lens) measured by intraoperative spectral-domain OCT (Catalys ® Precision System, Johnson & Johnson Vision); in these eyes, ELP displayed no correlation to intraoperative lens volume (Gouvea, et al, unpublished data, 2021).…”
mentioning
confidence: 94%
“…resbyopia affects approximately 1.8 billion people worldwide 1 (typically individuals aged >40 years) and is a characteristic of the age-related, progressive changes of the crystalline lens, or dysfunctional lens syndrome, which includes stage 1 (mild presbyopia and higher-order aberrations), stage 2 (lens opacity with advancing presbyopia and higher-order aberrations), and cataract with severe presbyopia and higher-order aberrations. 2,3 Presbyopia progressively reduces the eye's ability to focus on near objects, likely resulting from gradual lens thickening and loss of lens elasticity and accommodative ability [4][5][6][7][8][9] and can impact a person's daily activities, quality of life, and emotional well-being. 10 Advanced and absolute presbyopia also impair intermediate vision as the progressive loss of remaining accommodative ability prevents a wide range of clear vision, 11 and individuals with uncorrected presbyopia reported a significant impact on activities requiring near (reading, writing, and using smartphones) and intermediate (computer work or cooking) vision.…”
mentioning
confidence: 99%
“…Waring et al used Catalys' i-OCT to study possible correlations among ACD, LT, lens diameter (LD, the distance from the intersections of the anterior to posterior lens surfaces), and lens volume (LV, the volume of the lens calculated from the measured anterior and posterior lenticular surface curvatures that were extended to intersect in the lenticular periphery) [12]. While ACD and LT could be easily detected, LD and LV could be acquired only by i-OCT and were related to lens aging.…”
Section: Resultsmentioning
confidence: 99%
“…In their work, Waring et al showed that i-OCT could detect LV, LD, and LT and they provided regression equations to predict LD and LV from conventionally available parameters. The authors stated this additional info could help in effective lens position (ELP) estimate/ion (consequently improving IOL power calculation and enhancing refractive predictability) and, in new IOL technologies development, such as capsule refilling [12].…”
Section: Discussionmentioning
confidence: 99%